Proposta de melhoria do processo de treinamento em uma concessionária de caminhões, no estado da Paraíba - Souza, Gabrielle Ingrid Oliveira e (2022)
Aiming to follow both the market requirements and the management of people and knowledge, this work brings a reading about the training processes offered by a private company in the State of Paraíba, focusing mainly on internal training planned and organized by the institution itself. With the objective of evaluating the training process as a learning management tool, a documental survey was carried out, mapping the internal training processes and interviews with managers. For the collection of documentary data, the courses taken by all employees (headquarters and branch) were considered, and those who participated between 2019 and 2020 were selected. Bizagi Modeler program and analysis through ISO/TR26122. For the interviews, six managers from the four main sectors were selected, whose speeches were divided into the strengths and weaknesses of the training process. At the end of this work, the analyzes were transformed into a SWOT matrix that seeks to serve as a guide for the organization to implement improvements in its process. The main conclusion that we can draw from this study is that despite the existence of a physical structure, a team dedicated to the organization of training and constant investments in qualification, only these measures without knowledge of the training objectives, without determination of indices, without records of all actions of corporate education available and without adequate planning, lead to a lack of information about the impact of training on the results of the studied company.